Synthesis and biological evaluation of water-soluble esterase-activated CO-releasing molecules targeting mitochondria - Hemmersbach, Lars; Schreiner, Yannick; Zhang, Xinmiao; Dicke, Finn; Hünemeyer, Leon; Neudörfl, Jörg-Martin; Fleming, Thomas; Yard, Benito A.; Schmalz, Hans-Günther (Chemistry - a European journal, 2022)
Abstract Due to the beneficial effects of carbon monoxide as a cell-protective and anti-inflammatory agent, CO-releasing molecules (CORMs) offer some promising potential applications in medicine. In this context, we synthesized a set of acyloxy-cyclohexadiene-Fe(CO)3 complexes, all displaying a N-methyl-pyridinium triflate moiety in the ester side chain, as mitochondria-targeting esterase-triggered CORM prodrugs. Whereas the compounds in which the acyloxy substituent is attached to the 2-position of the diene-Fe(CO)3 unit (A series) spontaneously release CO upon dissolution in phosphate buffer, which remarkably is partly suppressed in the presence of porcine liver esterase (PLE), the 1-substituted isomers (B series) show the expected PLE-induced release of CO (up to 3?equiv.). The biological activity of Mito-CORMs 2/3-B and their isophorone-derived analogs 2/3-A?, which also displayed PLE-induced CO release, was assessed by using human umbilical vein endothelial cells (HUVEC). Whereas Mito-CORMs 2/3-B were not cytotoxic up to 500??M (MTT assay), Mito-CORMs 2/3-A? caused significant toxicity at concentrations above 50??M. The anti-inflammatory potential of both Mito-CORM variants was demonstrated by concentration-dependent down-regulation of the pro-inflammatory markers VCAM-1, ICAM-1 and CXCL1 as well as induction of HO-1 in TNFα-stimulated human umbilical vein endothelial cells (HUVECs; western blotting and qPCR). Energy phenotyping by seahorse real-time cell metabolic analysis, revealed opposing shifts of metabolic potentials in cells treated either with Mito-CORMs 2/3-B (increased mitochondrial respiration and glycolytic activity) or Mito-CORMs 2/3-A? (suppressed mitochondrial respiration and increased glycolytic activity). Thus, the Mito-CORMs represent valuable tools for the safe and targeted delivery of CO to mitochondria as a subcellular compartment to induce positive anti-inflammatory effects with only minor shifts in cellular energy metabolism. Also, due to their water solubility, these compounds provide a promising starting point for further pharmacological studies.
Online veröffentlicht: 30. Juni 2022
Gesehen am 25.09.2023